THE EFFECT OF STRATEGIC ORIENTATION ON THE BUSINESS PERFORMANCE OF CULINARY TRADERS IN BOGOR - Verawati Setiawan; Fahrul Riza (Universitas Pelita Harapan, 2022)
This study aims to analyze the effect of entrepreneurial orientation, growth orientation, and market orientation on the business performance of food and beverage business actors in Bogor with brand orientation as an intervening variable. The sample used in this study were all culinary traders in Suryakencana Bogor culinary tourism totaling 97 respondents. This study uses quantitative data analysis methods, the data analysis technique used is Partial Least Square-Structural Equation Modeling (PLS-SEM) using software SmartPLS version 3.3.9. The results of the analysis carried out stated that entrepreneurial orientation and growth orientation had a positive and significant effect on business performance. Market orientation is not having significant effect on business performance. Brand orientation has no mediating effect on entrepreneurial orientation, growth orientation, and market orientation on business performance.